Bringing in the future : strategies for farsightedness and sustainability in developing countries - Ascher, William (University of Chicago Press, 2009)
Humans are plagued by shortsighted thinking, preferring to put off work on complex, deep-seated, or difficult problems in favor of quick-fix solutions to immediate needs. When short-term thinking is applied to economic development, especially in fragile nations, the results--corruption, waste, and faulty planning--are often disastrous. In Bringing in the Future, William Ascher draws on the latest research from psychology, economics, institutional design, and legal theory to suggest strategies to overcome powerful obstacles to long-term planning in developing countries. Drawing on cases from Afri.